2004
DOI: 10.1093/rpd/nch111
|View full text |Cite
|
Sign up to set email alerts
|

Microdosimetric investigation at the therapeutic proton beam facility of CATANA

Abstract: Proton beams (62 Mev) are used by the Laboratori Nazionali del Sud of the Italian Institute of Nuclear Physics to treat eye melanoma tumours at the therapeutic facility called CATANA. A cylindrical slim tissue-equivalent proportional counter (TEPC) of 2.7 mm external diameter has been used to compare the radiation quality of two spread-out Bragg peaks (SOBP) at the CATANA proton beam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 2 publications
3
19
0
Order By: Relevance
“…These results were roughly consistent with the calculated RBE distributions reported in several previous papers [6, 7, 27]. Matsuura et al [28] reported that the experimental RBE value of HSG tumor cells at the Bragg peak for the mono-energetic 235-MeV proton beam was 1.18 ± 0.07 times higher than that at the plateau region and nearly independent of the dose rate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were roughly consistent with the calculated RBE distributions reported in several previous papers [6, 7, 27]. Matsuura et al [28] reported that the experimental RBE value of HSG tumor cells at the Bragg peak for the mono-energetic 235-MeV proton beam was 1.18 ± 0.07 times higher than that at the plateau region and nearly independent of the dose rate.…”
Section: Discussionsupporting
confidence: 91%
“…However, a systematical uncertainty in the water-equivalent depth of about ±1.5 mm was estimated in consideration of the spherical wall and placement accuracy of the TEPC in the water phantom. A miniature TEPC would be effective for measuring microdosimetric spectra around the beam range with higher resolution [27]. …”
Section: Discussionmentioning
confidence: 99%
“…10 Additionally, the group at INFN Legnaro laboratories has proposed the mini TEPC to avoid pile up and to assess the RBE of the radiation by linking the physical microdosimetric parameters with the corresponding biological response. The feasibility of the mini TEPC has previously been tested in a 62 MeV proton beam 17 and recently used for monenergistic 12 C ion beam at CNAO. 18 Studies using the TEPC for microdosimetric measurements for both in-field and out-of-field in low dose rate 12 C and 7 Li ion pencil beams have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…To validate the operation of the micro-calorimeters and, in the future, to investigate the assumption made in ionisation-based microdosimeters that there is a proportionality between ionisation and energy deposition, comparisons will be performed with a silicon-microtelescope [12,13] and a mini-TEPC [14] that both have been tested extensively in proton beams [15,16].…”
Section: Microdosimetrymentioning
confidence: 99%